SOURCING DECISIONS TO MITIGATE SUPPLY CHAIN DISRUPTION RISKS: CASE STUDY OF A LEATHER MANUFACTURER - Hsu, Ching Fen (2005)
Modern supply chains are international, complex, dynamic networks that are subject to uncertainty, vulnerability, large time-lags, and variability in delivery. One of the main reasons that have made supply chain networks more vulnerable is the raise of lean or JIT manufacturing practices. Those approaches are to eliminate all the wastes in supply chains and focus greatly on cost reduction by centralising the assets, reducing the supplier base or decreasing the stocks dramatically. However, the benefits must be weighed and balanced against the future risks of disruptions and costs. Furthermore, since sourcing policy is closely relative to supply chain continuity and security, this study examines how sourcing decisions in one large-scale leather manufacturing organisation could help mitigate supply chain disruption risks, focusing on identifying and examining key factors which have great impact on sourcing decision making processes to figure out the most appropriate sourcing policy for organisations to mitigate supply chain disruption risks.